Interleukin-37 is involved in the immunopathogenesis of infectious mononucleosis - Mingsheng Zhao; Li Ma; Huihui Jiang; Yufeng Gu; Xin Yang; Riming Liu; Chengming Sun; Yulan Li (Italian Journal of Pediatrics, 2023)
Abstract Background Multiple immunopathological responses to viruses are observed in infectious mononucleosis (IM), a manifestation of primary infection with Epstein-Barr virus (EBV). Protective effects of the negative immunoregulatory molecule interleukin-37 (IL-37) have been observed in various bacterial and viral infections. However, the function of IL-37 in IM remains unknown. Methods Flow cytometry and enzyme-linked immunosorbent assay (ELISA) were used to determine the expression of IL-37 in the peripheral blood of patients diagnosed with IM, and the variation of lymphocyte subsets. Furthermore, the associations between IL-37 expression and the percentage of lymphocyte subgroups were analyzed. Results Patients with IM had severe immune dysfunction. The control group had a lower expression of IL-37 than the patients with IM. There were significant associations between IL-37 expression and both the proportion of CD3+T cells and the ratio of CD3+CD4+ to CD3+CD8+T cells. Patients with higher levels of IL-37 expression had lower levels of the liver inflammation indicators, alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Conclusions IL-37 may affect the immune pathogenesis of patients with IM infected with EBV, and may have immunotherapeutic benefit for EBV-associated illnesses.